Identification and Diversity of Mycorrhizae in Several Rhizosphere Vegetation Plants in Former Mining Land for Gambir Planting - Rangga Arnelio; Aprizal Zainal; Benni Satria (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2025)
Post-mining land represents an ecosystem that has undergone severe degradation as a result of mineral resource exploitation. The mining process causes the loss of the topsoil layer, which is rich in organic matter, microorganisms, and essential nutrients, leading to nutrient-poor, compacted, and acidic soils that are often contaminated with heavy metals. The cultivation of gambier has been proposed as a strategy to optimize the use of post-mining land. One initial approach to address this problem is the application of arbuscular mycorrhizal fungi (AMF). Soil conditions and the type of host vegetation strongly influence the diversity of AMF in post-mining areas. Therefore, identifying the presence of AMF in post-mining soils is necessary. Soil samples were collected from PT Atoz Nusantara Mining, located in Kenagarian Tambang, IV Jurai Subdistrict, Pesisir Selatan Regency. This exploratory study involved soil analysis and the identification of arbuscular mycorrhizal fungi. The plant species sampled included alang-alang (Imperata cylindrica), resam nail (Dicranopteris linearis), caramunting (Melastoma malabathricum), telang (Clitoria ternatea), sedge grass (Cyperus rotundus), and sembung (Blumea balsamifera). The results indicated that the occurrence of mycorrhizae in the rhizosphere varied across post-mining sites, with identified species including Acaulospora sp., Glomus sp. 1, Glomus sp. 2, Sclerocystis sp., and Gigaspora sp. These mycorrhizae demonstrate potential for restoring soil fertility in post-mining areas.